The prevalence and effects of occupational licensing - Morris M. Kleiner; Alan B. Krueger (Institute for the Study of Labor (IZA), 2008)
This study provides the first nation-wide analysis of the labor market implications of occupational licensing for the U.S. labor market, using data from a specially designed Gallup survey. We find that in 2006, 29 percent of the workforce was required to hold an occupational license from a government agency, which is a higher percentage than that found in studies that rely on state-level occupational licensing data. Workers who have higher levels of education are more likely to work in jobs that require a license. Union workers and government employees are more likely to have a license requirement than are nonunion or private sector employees. Our multivariate estimates suggest that licensing has about the same quantitative impact on wages as do unions - that is about 15 percent, but unlike unions which reduce variance in wages, licensing does not significantly reduce wage dispersion for individuals in licensed jobs.
urn:nbn:de:101:1-2008092334
Keywords: J8; 330; Occupational licensing; regulation; wages; Arbeitsmarkt; Beruf; Konzession; Genehmigung; Gewerkschaftsbewegung; USA